Challenges of Implementing Agile Methodology in the Jordanian Banking Sector - Alaraj, Abdal Hafeth (European Scientific Journal, ESJ, 2025)
Traditional banking operations must change because financial industry dynamics and customer demands have started to transform the market. Financial institutions use Agile methods which were created for software development to increase operational efficiency while boosting customer satisfaction levels. Jordanian banks face various obstacles in Agile implementation which stem from banking employees’ resistance to change and from regulatory requirements and legacy system integration complexities as well as low Agile skill levels within banking organizations. Decision-making patterns that enforce hierarchy act as an obstacle to the implementation process. This research combines interviews of banking experts and surveys to study Agile implementation in Jordanian banks through a mixed-methods approach. The study identifies important barriers that lead to proposed solutions including professional training for selected positions as well as top-level executive backing and stepwise rollouts. The solutions to these problems will enable Jordanian banks to gain agility and competitiveness as well as innovation potential. The study advances knowledge about Agile adoption in literature while presenting usable recommendations for financial institutions. Survey results show resistance to change was the highest barrier at 75% of Jordanian banking employees, then followed by insufficient training as the highest issue at 50%. Moreover, 45% of the participants struggled to implement Agile with existing banking systems​. These remarks highlight formal Agile transformation approaches, including specialized training programs and executive-level sponsorship.